1998 IEEE International Reliability Physics Symposium Proceedings 36th Annual (Cat No 98CH36173) RELPHY-98 1998
DOI: 10.1109/relphy.1998.670449
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of highly accelerated Q/sub bd/ tests to TDDB life tests for ultra-thin gate oxides

Abstract: A new technique is proposed to extract long-term constant voltage stress time-dependent dielectric breakdown (TDDB) acceleration parameters from highly accelerated constant or ramped current injection breakdown tests. It is demonstrated that an accurate correlation of highly accelerated breakdown tests to long-term constant voltage TDDB tests can be obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Interface trap generation has been seen to be proportional to the exp (v) [490] and, particularly in thinner oxides where the electron energy at the anode is proportional to the gate voltage, time-to-breakdown has been found to be proportional to the exp (V) [522,541,547,635,[846][847][848][849][850][851][852]. Most of the long-time, low-voltage studies of breakdown have shown that the time-to-breakdown is very well fit by an exp (E) relationship, especially at lower voltages [24,102,145,264,265,626,656,660,711,753,820,[853][854][855][856][857][858][859][860][861][862][863][864][865]. It has often been observed that the field acceleration factor in thicker oxides is about 10 MV/cm/decade-in-time [24,626,656,660,753,855].…”
Section: Reliabilitymentioning
confidence: 99%
“…Interface trap generation has been seen to be proportional to the exp (v) [490] and, particularly in thinner oxides where the electron energy at the anode is proportional to the gate voltage, time-to-breakdown has been found to be proportional to the exp (V) [522,541,547,635,[846][847][848][849][850][851][852]. Most of the long-time, low-voltage studies of breakdown have shown that the time-to-breakdown is very well fit by an exp (E) relationship, especially at lower voltages [24,102,145,264,265,626,656,660,711,753,820,[853][854][855][856][857][858][859][860][861][862][863][864][865]. It has often been observed that the field acceleration factor in thicker oxides is about 10 MV/cm/decade-in-time [24,626,656,660,753,855].…”
Section: Reliabilitymentioning
confidence: 99%
“…Interface trap generation has been seen to be proportional to the exp' v) [490] and, particularly in thinner oxides where the electron energy at the anode is proportional to the gate voltage, time-to-breakdown has been found to be proportional to the exp (V) [522,541,547,635,[846][847][848][849][850][851][852]. Most of the long-time, low-voltage studies of breakdown have shown that the time-to-breakdown is very well fit by an exp <E) relationship, especially at lower voltages [24,102,145,264,265,626,656,660,711,753,820,[853][854][855][856][857][858][859][860][861][862][863][864][865]. It has often been observed that the field acceleration factor in thicker oxides is about 10 MV/cm/decade-in-time [24,626,656,660,753,855].…”
Section: Reliabilitymentioning
confidence: 99%
“…Bearing this concept of equivalence in mind, this leads one to the question of whether the information between each stress level during a linear ramped test can be used in a similar manner-that is, by using the information found between each stress level of a single distribution instead of between constant stress distributions. 1. Schematic of the failure probability that results for three single (V step1 , V step2 , andV step3 ) constant stresses and those that results when the stresses are applied in a sequence (V = stepped stress).…”
Section: Equivalence Conceptmentioning
confidence: 99%
“…However, since the 95% prediction intervals of both lifetime extrapolations do overlap, this technique is very promising to be of great use for fast feedback results during development, qualification, and process control. For comparison, the model accuracy of Chen et al [1] was demonstrated by varying γ values by ±1% and by a log(t 50 ) versus E ox plot; the model accuracy of Mullen et al [2] was shown by fits through their data. The Weibull shape parameter was not explicitly given in both cases, although it was shown here that the shape parameter calculated from ramped tests is strongly dependent on the original distribution.…”
Section: Lifetime Extrapolationmentioning
confidence: 99%
See 1 more Smart Citation